A REVIEW ON ISLAMOPHOBIA AND ITS PRACTICES IN INDONESIA AS MUSLIM-MAJORITY COUNTRY - Muhammad Rasyid Ridho; Siti Zainurrahmi Br Bangun (Program Pascasarjana UIN Sumatera Utara, 2025)
This research paper explores the phenomenon of Islamophobia, particularly its manifestations and implications in Indonesia. The study critiques the predominant Western-centric scholarship on Islamophobia, highlighting its existence has also developed in Muslim-majority countries. It delves into the historical and contemporary perspectives on Islamophobia in global settings, especially from Muslim-majority countries to within Indonesia, especially the socio-political dynamics from the Old Order through the New Order to the post-Reformation era. Drawing on qualitative analysis, the paper discusses various incidents and policies that reflect Islamophobic tendencies, such as governmental restrictions on Islamic expressions by banning civil society oganizations such as Hizbut Tahrir Indonesia (HTI) and Islamic Defender Front (FPI), the reemeergence of niqab and short trousers (celana cingkrang) prohibition in state agencies, and dai certification. There is a few case on societal prejudices against Muslims in horizontal level. There is need for dialogue and understanding among Muslim communities and advocates for the role of religious authorities in countering misinformation and fostering a narrative of tolerance and inclusivity due to Islamophobia potential impact on society cohesiveness. Ultimately, it calls for a collective effort to address Islamophobia in Indonesia while promoting the values of Wasathiyyah Islam as a guiding principle for harmonious coexistence.